ROLAND BARTHES SEMIOTIC STUDY: UNDERSTANDING THE MEANING WORD OF 'AZAB, A REINTERPRETATION FOR MODERN SOCIETY - Adiansyah, Ridho; Sofia, Adib; Bensar, Muin; Adams, Ali; Barakat, Mohamed Ahmed (Universitas Muhammadiyah Surakarta, 2023)
Modern society's understanding of the meaning of Azab is often inaccurate; many understand it as torture, cruelty, and God's retribution. This article was created to examine how the concept of Azab is understood and perceived by Muslims. Because most know Azab as torment, pain, and God's cruelty, Roland Barthes' semiotics will be used as a knife to find out how the true meaning of doom from the Qur'an relates to this topic for analysis. Barthes argues that all language systems can be understood through two steps: the first is known as the linguistic system (linguistics), and the second is known as the myth system (mythology). To achieve the myth system, namely by using a sign system consisting of three components: the signifier, the signified, and the sign on the second level. Using Roland Barthes' semiotics, the concept of Azab, understanding that God will torture humans who have sins in the afterlife, is just a myth. Punishment is not a form of His wrath but a form of His love. God has given His servant signs of Azab as proof of nature rahman and womb Him so that humans do not get that painful Azab. Even though, in the end, a sinful human still gets punishment (torture) as a reward for his actions, all of this is because God wants to purify and cleanse humans from sins while living in the world.